KAPABILITAS DAN PENGUATAN FUNGSI BANK SAMPAH INSPIRASI MADANI - Rizky Dianda Saputra; Siti Sofro Siddiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Waste banks are one of the solutions for effective and sustainable waste management. This study aims to indentify and analyze the activites and challenges of Bank Sampah Inspirasi Madani in optimizing the function of waste banks. This research uses a qualitative research method. Data collection in this study involved direct observation, indepth interviews, and documentation. Subjects in this study amounted to 6 people. The result of this study show that Bank Sampah Inspirasi Madani has carried out various activities in optimizing the function of waste banks, including waste collection, waste sorting, waste sales, education and socialization, as well as collaboration with waste suppliers and buyers. This waste bank has also faced several challenges, including the lack of public awareness about the importance of waste management, insufficient members, and constraints in waste marketing. Despite these challenges, this waste bank has the potential to continue growing and providing significant benefits in waste management. Efforts to strengthen capabilities and improve coorperation between waste banks, the government, and the community are needed to achieve sustainable waste management goals. Keywords: waste bank, Capability, function strengthening